ChemInform Abstract: Transformation and Storage of Solar Energy: Photochemistry and ‐catalysis for Future Energy Supply. Issue 39 (23rd September 2014) - Haessner, Carmen; Koehler, Klaus; Wussow, Katharina
Abstract Review: 39 refs.